(Na,Ca)(Ti3+,Mg)Si2O6-clinopyroxenes at high pressure: influence of cation substitution on elastic behavior and phase transition - Ullrich, Angela; Miletich, Ronald; Balic-Zunic, Tonci; Olsen, Lars; Nestola, Fabrizio; Wildner, Manfred; Ohashi, Haruo (Physics and chemistry of minerals, 2010)
A compressional study of (Na,Ca)(Ti3+,Mg)Si2O6-clinopyroxenes was carried out at high pressures between 10−4 and 10.2 GPa using in situ single-crystal X-ray diffraction, Raman spectroscopy and optical absorption spectroscopy. Compressional discontinuities accompanied by structural changes, in particular, the appearance of two distinct Ti3+-Ti3+ distances within the octahedral chains at 4.37 GPa, provide evidence for the occurrence of a phase transition in NaTi3+Si2O6. Equation-of-state parameters are K0 = 115.9(7) GPa with K′ = −0.9(3) and K0 = 102.7(8) GPa with K′ = 4.08(5) for the low- and high-pressure range, respectively. The transition involves a C2/c-P$$ \overline{1} $$symmetry change, which can be confirmed by the occurrence of new modes in Raman spectra. Since no significant discontinuity in the evolution of the unit-cell volume with pressure has been observed, the transition appears to be second-order in character. The influence of the coupled substitution Na+Ti3+↔Ca2+Mg2+ on the static compression behavior and the structural stability has been investigated using a sample of the intermediate composition (Na0.54Ca0.46)(Mg0.46Ti0.54)Si2O6. No evidence for a deviation from continuous compression behavior has been found, neither in lattice parameter nor in structural data and the fit of a third-order Birch-Murnaghan equation-of-state to the pressure-volume data yields a bulk modulus of K0 = 109.1(5) GPa and K′ = 5.02(13). Raman and polarized absorption spectra have been compared to NaTiSi2O6 and reveal major similarities. The main driving force for the phase transition in NaTi3+Si2O6 is the localization of the Ti3+d-electron and the accompanying distortion, which is suppressed in the (Na,Ca)(Ti3+,Mg)Si2O6-clinopyroxene.
Im Titel ist "3+" hochgestellt und die Ziffern "2" und "6" sind tiefgestellt
Online veröffentlicht: am 24 Mai 2009
Gesehen am 26.01.2024